TRPM2, PDLIM5, BCL3, CD14, GBA Genes as Feasible Markers for Premature Coronary Heart Disease Risk - Prasongsukarn, Kriengchai; Dechkhajorn, Wilanee; Benjathummarak, Surachet; Maneerat, Yaowapa (Frontiers in Genetics, 2021)
Background: Beyond non-genetic risk factors, familial hypercholesterolaemia (FH) plays a major role in the development of CHD. FH is a genetic disorder characterized by heritable and severely elevated levels of low-density lipoprotein (LDL) cholesterol, which can lead to premature cardiovascular disease, particularly familial coronary heart disease (FH-CHD). Method: To explore genes indicating a risk of familial (premature) coronary heart disease (FH-CHD) development in FH, 30 Thai male volunteers were enrolled: 7 healthy controls (N), 6 patients with hypercholesterolaemia (H), 4 with FH, 10 with CHD, and 3 with FH-CHD. Transcriptome data were investigated using next-generation sequencing analysis in whole blood (n = 3). Genes that were significantly expressed in both FH and FH-CHD, but not in N, H, and CHD groups, were selected and functionally analysed. Results: The findings revealed that 55 intersecting genes were differentially expressed between FH and FH-CHD groups. Ten of the 55 genes (MAPK14, TRPM2, STARD8, PDLIM5, BCL3, BLOC1S5, GBA, RBMS1, CD14, and CD36 were selected for validation. These 10 genes play potential roles in chronic inflammation and are involved in pathways related to pathogenesis of CHD. Using quantitative real-time PCR, we evaluated the mRNA expression of the selected genes in all 30 volunteers. TRPM2, PDLIM5, BCL3 were significantly upregulated and GBA was significantly downregulated in both FH and FH-CHD compared with the N, H, and CHD groups. Conclusion: our preliminary investigation reveals that the TRPM2, PDLIM5, BCL3, and GBA genes may have potential for further development as predictive markers for FH-CHD.